SPEECH ANALYSIS (DISCOURSE SEMANTIC ANALYSIS BASED ON SYSTEMIC FUNCTIONAL LINGUISTICS THEORY) - Hieronimus Canggung Darong; Sebastianus - Menggo; Maria Olga Jelimun (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2022)
This study is concerned with discourse semantic analysis of three selected victory speeches of the US Presidents. It was conducted for and aimed at describing, explaining, and analyzing the field, the interpersonal meaning (tenor) the mode of the texts, the schematic structure, and the unity of the texts by using Systemic Functional Linguistics (SFL) as the basis of analysis. The speech texts were changed into clauses and then analyzed. The results of the analysis found that the register category of field is similar. The transitivity patterns of the grammar, reference, and lexical string analysis share common features that is the realization of experiential action done by the speaker and audience for the progress of America. The interpersonal meaning of the texts is slightly different, in which, Joe Biden and Barack Obama established an intimate relationship with the audience, while in Donald trump’s text, the sense of intimacy and the distance with the audience are far. Since the nominal groups used were simple, the mode of all texts belongs to the spoken mode. Besides, In terms of schematic structure, the texts were constructed similarly consisting of an introduction, body, and conclusion. Finally, this study also found that the anaphoric reference which was predominantly used, a good pattern of conjunction relations, and lexical relations between lexical items appearing cross clauses categorize the texts as being highly cohesive.